The Effectiveness of Teacher Performance Management in the Implementation of Student Learning - Medi Yansyah (Journal Corner of Education, Linguistics, and Literature, 2022)
The teacher's role in the process of providing education is very dominant to be implemented. Every educational institution must be able to have competitiveness that can be demonstrated through improving the quality of education services. Therefore, efforts in the process of improving human resources, in this case, professional teachers, need concrete affirmation, to carry out their roles and duties. The purpose of this study was to determine the effectiveness of teacher performance management in the process of implementing student learning at Madrasah Ibtidaiyah Nurul Asyrof Teluk Betung Barat Bandar Lampung. This research is qualitative research, with a descriptive approach that aims to obtain information about the effectiveness of teacher performance management in the process of implementing student learning at Madrasah Ibtidaiyah Nurul Asyrof Teluk Betung Barat, Bandar Lampung. While the data was obtained through the method of observation, documentation, and interviews. The results of this study explain the effectiveness of teacher performance management in the process of implementing student learning at Madrasah Ibtidaiyah Nurul Asyrof Teluk Betung Barat Bandar Lampung by the planning, implementation, and evaluation process can run well.